Evaluation of motivation of pencak silat athletes In Padang City - Tjung Hauw Sin; Fakhrina Hudayani (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The problem in this study is the low motivation of athletes to exercise. The purpose of the study was to determine the motivation of the pencak silat athletes in the city of Padang. This research uses descriptive. The population in this research is the pencak silat athletes from Padang City. Sampling using purposive sampling. The research data analysis technique uses a frequency distribution technique with the calculation of the percentage P = F / N × 100%, or = 0.05. Based on the results of 26 (100%) athletes. Those who have a very good category are 9 athletes or (34.6%), who have a good category are 17 athletes or (65.4%), who have a moderate category are 0 athletes or (0.0%), who have a poor category 0 athletes or (0.0%) and those who have a category less than 0 athletes or (0.0%)